SAT0100 IN THE ABSENCE OF GUIDELINES, HOW ARE RHEUMATOLOGISTS MANAGING ANTI-CCP POSITIVE PATIENTS WITHOUT CLINICAL SYNOVITIS?. (June 2019) - Mankia, Kulveer; Briggs, Christopher; Emery, Paul
Abstract : Background: The emphasis on early referral and treatment of rheumatoid arthritis (RA) means rheumatologists are now seeing patients earlier in the natural history of RA. Despite clear guidelines for the management of early arthritis, there are no guidelines on how to manage anti-CCP positive (CCP+) patients with symptoms but no clinical synovitis who are at-risk of developing RA. Given the frequent use of ultrasound (US) in early arthritis clinics, we hypothesised that imaging is being used by rheumatologists to guide the management of these at-risk patients. Objectives: To survey national practice to identify, in the absence of any guidelines, how CCP+ patients without clinical synovitis are being managed by rheumatologists in the UK and specifically to investigate how imaging is being used to guide management in the 'pre-arthritis' phase of RA. Methods: Anonymous questionnaires were completed by rheumatologists at a national rheumatology meeting focused on recent advances in rheumatology (Revolutions in Rheumatology 2018, London, UK) and at regional general rheumatology meetings in Yorkshire, UK. Results: Questionnaires were returned from 47 consultant rheumatologists working in 39 different UK hospitals. 44/47 (94%) rheumatologists reported they are referred CCP+ patients who have musculoskeletal (MSK) symptoms but no clinical synovitis in their routine clinical practice. Of these, 32/44 (73%) were referred ≥5 patients per year. In CCP+ patients with 'inflammatory symptoms' but no clinical synovitis, 36/44 (82%) would request an US scan to help guide management and 2/44 (5%) would request an MRI scan. All respondents would follow these patients regularly and 5/44 (11%) would consider a clinical trial. In CCP+ patients with 'non-inflammatory' symptoms and no clinical synovitis, 18/44 (41%) would request an US scan, 13/44 (30%) would observe in clinic and 12/44 (27%) would discharge back to primary care. When specifically asked about use of high-resolution imaging in CCP+ patients without clinical synovitis, 40/44 (91%) reported they used imaging, with most (37/40, 93%) using US. In patients where power Doppler (PD) signal is present on US in at least one joint, most (55%) would start disease-modifying anti-rheumatic drug (DMARD) treatment (figure 1 ) and 16% would treat according to RA guidelines. In patients with US tenosynovitis but no US synovitis, most (73%) would treat with either corticosteroids alone (48%) or a DMARD (48%). In contrast, in patients with no US synovitis or US tenosynovitis, 23/37 (62%) would observe without therapy while 12/37 (32%) would discharge the patient (figure 1 ). Conclusion: UK rheumatologists are routinely referred CCP+ patients in the pre-arthritis phase of RA and often treat these patients with synthetic DMARDs, guided by US findings. Whether this pragmatic approach is an appropriate one needs to be tested in clinical trials with RA prevention as the ultimate ambition. Guidance on management of these patients would clearly be helpful. Disclosure of Interests: Kulveer Mankia Grant/research support from: Research support from BMS and Lilly, Speakers bureau: Honoraria from Abbvie, UCB, Christopher Briggs: None declared, Paul Emery Grant/research support from: Pfizer, MSD, AbbVie, Bristol-Myers Squibb, Roche, Consultant for: Pfizer, MSD, AbbVie, Bristol-Myers Squibb, UCB, Roche, Novartis, Gilead, Samsung, Sandoz and Lilly